(untitled) (Jurnal Agribisnis dan Agrowisata, 2026)
Mechanism and performance analysis of organic white rice supply chain in PT. Bali Sri Organik Badung Regency. Organic rice is an important food commodity because it is a staple food for people, especially in Bali. There is a gap between demand and supply for organic rice, especially organic white rice, so it is necessary to pay attention to the chain cycle that moves from producers to final consumers. The condition and management of the organic white rice supply chain is an important aspect that needs to be considered to maintain its continuity and availability, so as to achieve a balance between demand and supply of organic white rice. The purpose of this study was to analyze the supply chain mechanism for organic white rice and to analyze the performance of the supply chain for organic white rice in PT. Bali Sri Organik, Badung Regency. Identification of supply chain mechanisms for organic white rice was carried out through interviews which were then analyzed using the Food Supply Chain Networking (FSCN) and measurement of supply chain performance by looking at margins and marketing efficiency of the organic white rice supply chain. The research results show that the marketing target for organic white rice is the domestic market, the organizational structure consists of partner farmers as grain suppliers, Bali Sri Organik as producers, wholesalers and retailers. The transaction system with partner farmers is pay later in cash and wholesalers and retailers in the form of invoices. The ordering system is carried out by pre-order, the process of distributing goods and paying transportation costs is carried out by Bali Sri Organik to wholesalers and retailers. The performance of the organic white rice supply chain is based on efficient marketing margin in channel 1. Meanwhile, marketing efficiency is efficient in every channel, because each institution in the supply chain has allocated its marketing costs well.